Analisis Pemikiran Muhamad Tentang Efisiensi Harga Murabahah di Perbankan Syari’ah - Husna, Aftina Nurul (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2025)
This study aims to find out the murabahah pricing technique based on Muhammad's thoughts and the impact of its application on the efficiency of murabahah prices in sharia banking. The research method used is literature research. The data collection technique uses the documentation method and structured interview. The results of this study show that the murabahah pricing technique currently used in sharia banking operations does not meet the criteria for sharia compliance because it contains elements of price ghara. Muhamad as an academic as well as a practitioner of sharia banking, proposed a new formula for setting murabahah prices as an answer to his anxiety about the irregularities in the old formula. Although the new formula has not been widely used, this formula can increase the efficiency of murabahah prices in Islamic banking, especially if the Islamic bank has a large scale and when there is a financing restructuring.